Conceptualizing Islamic Brand Engagement - Chandra Warsito (Ijtimā`iyya: Journal of Muslim Society Research, 2019)
This study aims to conceptualize the Muslim Customer Engagement of Islamic Brands towards Muslim customer loyalty. An in-depth review of literature was carried out to develop this concept, in order to provides a foundation for further researches. This study shows that the Islamic brands could optimize the loyalty of Muslim customer. In addition to this, this research is also expected to be able to provide a brief overview of profitable opportunities in Islamic market business in Indonesia, especially entrepreneurs, marketers and retailers in building an accurate marketing strategies. In terms of customer loyalty, business owners or management need to identify variables that influence this factor, and so this research is also useful in providing new construction, which could be tested and are useful for studying the characteristics of Muslim customer and market. Hopefully this research could fill the literature gaps in Muslim customer behavior study in Indonesia.